RATIONALITY OF STUDENTS IN INVESTING - Widyaningrum, Ajeng Sekar; Mukhlis, Imam (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
This research aims to assess rational or irrationalstudent investment decision actions throughthe influence of financial literacy, socio-economic factors and financial technology students of the Faculty of Economics and Business, State University of Malang on investment decisions.This study used students of the Faculty of Economics and Business, State University of Malang class of 2019 as the population using the purposive sampling method so that 110 samples were obtained. Data collection techniques in this study used a Google form questionnaire. The collected data were analyzed using the path analysis method with SmartPLS software. The results of the analysis show that financial literacy and socio-economic factors have a significant effect on investment decisions, while financial technology has no effect on investment decisions.